SHP2 is essential for the progesterone-promoted proliferation and migration in breast cancer cell lines - Hui-Chen Wang; Hui-Chen Wang; Wen-Sen Lee; Wen-Sen Lee; Wen-Sen Lee; Wen-Sen Lee (Frontiers in Endocrinology)
IntroductionWe previously demonstrated that progesterone (P4) can promote breast cancer cell proliferation and migration through activating the P4 receptor (PR)/cSrc-mediated signaling pathway. It has been suggested that high level of Src homology region 2 domain-containing phosphatase-2 (SHP2) might be involved in breast oncogenesis. This study aimed to investigate whether SHP2 is involved in the P4-mediated cSrc activation in breast cancer cells.MethodsT47D, MCF-7 and BT-483 breast cancer cell lines were used in this study. Cell proliferation and migration were examined using MTT technique and wound healing assay, respectively. Immunoprecipitation assay and Western blot analysis were performed to evaluate protein-protein interaction and protein expression, respectively. Small interfering RNA (siRNA) technique was used to knock down protein expression.ResultsKnockdown of SHP2 expression abolished the P4-promoted cell proliferation and migration in T47D, MCF and BT-483 cell lines, suggesting that presence of SHP2 is essential for the P4-increased proliferation and migration of breast cancer cell lines. P4 (50 nM) treatment increased the complex formations of PR-cSrc-SHP2-caveolin-1, SHP2-p140Cap, and SHP2-Csk, and the level of p-cSrcY416 (activated form of cSrc). However, knockdown of SHP2 expression increased the complex formations of PR-cSrc-caveolin-1-Csk-p140Cap and the levels of p-caveolin-1, p-Csk and p-cSrcY527 (inactivated form of cSrc).DiscussionOur data suggest that SHP2 can bind to cSrc-negative regulatory proteins (p140Cap and Csk), hence preventing the interaction between cSrc and cSrc-negative regulatory proteins, leading to decreased phosphorylation of cSrc Y527 and prolonged cSrc activation. These findings highlight the role of SHP2 in the P4-promoted breast cancer cell proliferation and migration.